New validated stability indicating gradient rp-hplc method for the assay &related substances of miconazole nitrate and assay of benzoic acid in miconazole nitrate 2.0% w/w gel - S.KUMARAVEL; P.SHANMUGAPANDIYAN (International Journal of Pharma and Bio Sciences, 2017)
An innovative, simple, economic, selective and sensitive of the stability indicating gradient reverse phase high performance liquid chromatography (RP-HPLC) method has been developed and validated for the analysis of assay of Miconazole nitrate and Benzoic acid and related substances of Miconazole nitrate in gel dosage form with better precision and accuracy. Miconazole nitrate & Benzioc acid are found to be degraded together under different set of conditions as followed according to ICH guidelines and the degradants so formed along with Miconazole nitrate organic impurities were separated by using INERTSIL ODS C18(150mm x 4.6, 3.5µ) column in gradient mode with mobile phase A consisting of 0.1% v/v solution of phosphoric acid in water and mobile phase B consisting of water : acetonitrile (22:78) with a flow rate of 1.0 mL/min and throughout the gradient program with an UV detection wavelength of 227nm for both the compounds with an injection volume of 10µL.Its chromatographic run time was 15.0 min. The method was validated according to ICH guidelines with respect to all validation parameters such as selectivity, specificity, linearity, precision, accuracy, robustness and limits of detection and quantification. All parameters examined were found to be well within the stated guidelines. The results were indicating the method is selective and specific in analysis of both Miconazole nitrate & Benzioc acid in the presence of degradation products formed under various stress conditions. The Proposed Gradient RP-HPLC method is utilized for the simultaneous estimation of Assay of Miconazole nitrate and Benzoic acid and related substance determination in Miconazole Nitrate Gel.